An Elevated Peripheral Blood Monocyte-to-Lymphocyte Ratio Predicts Poor Prognosis in Patients with Primary Pulmonary Lymphoepithelioma-Like Carcinoma. - Liang Wang (PLoS ONE, 2015)
Primary pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare type of non-small cell lung cancer. In this study, we retrospectively reviewed the data from 74 consecutive patients with pulmonary LELC and investigated the prognostic value of pretreatment monocyte-to-lymphocyte ratio (MLR). The cut-off value determined by ROC curve for MLR was 0.262. According to this cut-off value, 36 (48.6%) patients had lower MLR value (<0.262) at diagnosis. There was no significant correlation between MLR level and gender, age, smoking history, stage, and lactate dehydrogenase (LDH) level. The 2-year, 5-year, and 10-year OS rate were 86%, 72%, and 61%, respectively; the 2-year, 5-year, and 10-year PFS rate were 71%, 63%, and 49%, respectively. In univariate analysis, advanced stage, elevated LDH level, and higher MLR value (> = 0.262) were significantly associated with poor OS and PFS. In a multivariate Cox regression model that included stage, LDH and MLR level, all of these three factors were found to be independent prognostic factors for both PFS and OS. In patients who received radical surgery, MLR level remained significantly correlated with OS and PFS. In conclusion, we firstly demonstrated that pretreatment MLR can be used as a useful independent prognostic marker in patients with pulmonary LELC, and might guide us to optimize the treatment strategies. However, due to the relatively rarity of this disease and the limitation of a retrospective study, further prospective studies performed in multicenter are necessary to validate the prognostic value of MLR in pulmonary LELC.